Apartment women : a novel - Ku, Pyŏng-mo, 1976- (Hanover Square Press, 2024)
"When Yojin moves with her husband and daughter into the Dream Future Pilot Communal Apartments, she's ready for a fresh start. Located on the outskirts of Seoul, the experimental community is a government initiative designed to boost the national birth rate. Like her neighbors, Yojin has agreed to have at least two more children over the next ten years. Yet, from the day she arrives, Yojin feels uneasy about the community spirit thrust upon her. Her concerns grow as communal child care begins and the other parents show their true colors. Apartment Women traces the lives of four women in the apartments, all with different aspirations and beliefs. Will they find a way to live peacefully? Or are the cultural expectations around parenthood stacked against them from the start? A trenchant social novel from an award-winning author, Apartment Women incisively illuminates the unspoken imbalance of women's parenting labor, challenging the age-old assumption that "it takes a village" to raise a child"--